3-Arylsydone and 4-Acetyl-3-Arylsydone: In vitro cytotoxicity against prostate cancer cell line (PC3), structure-activity relationship and in silico evaluation of their caspase 3 inhibition - Mohammed Abdualkader, Abdualrahman; Bakhtiar, M. Taher; Muhamad, Azira; Nik Yusoff, Nik Mohd. Idris (2016)
The increased rates of cancer encouraged scientists to look for new potent anticancer agents. Sydnone derivatives were found to have a wide range of biological activities, including antitumor and antimicrobial. This research aimed to evaluate the cytotoxicity of some sydnones against prostate cancer and to investigate their binding interaction with the apoptotic enzyme caspase 3. 3-arylsydnones were prepared as described in the literature by the cyclization of the corresponding nitroso compounds. The sydnone rings were then acetylated using acetic acid in the presence of phosphorous pentoxide. The cytotoxicity was determined in vitro against prostate cancer cell line (PC3) using MTT cell viability assay. The interaction mode between sydnones and caspase 3 was evaluated by molecular docking approaches using Autodock 4.2. Ten independent docking runs were carried out for each ligand and docking results were evaluated using the calculated free binding energy.It was found that sydnone compounds showed cytotoxic activity against PC3 cell line. 3-(4-chlorophenyl)sydnone and 3-(4-nitrophenyl)sydnone were the most active compounds having IC50 of 0.91 and 0.36 mM. On the other hand, 3-(4-hydroxymethylphenyl)sydnone showed the lowest cytotoxic activity with IC50 of 11.56 mM. Structure activity relationship postulated that the existence of acetyl group at C4 of the sydnone ring resulted in a dramatic decrease of the biological activity. Electron withdrawing and hydrophobic substituents at the para position of the phenyl ring were found to enhance the bioactivity of both 3-arylsydnon and their acetylated analogues. The docking result demonstrated that 9 molecules had hydrogen bonds with the active site of caspase 3 which consists Arg207 and Arg64. The findings of this study indicated that sydnones are promising cytotoxic compounds for the treatment of prostate cancer and merit more studies to investigate their activity against other cancer cell lines along with in vivo evaluation.